Ultrasonic cavitation at liquid/solid interface in a thin Ga–In liquid layer with free surface - Zhengwei Li; Zhiwu Xu; Degang Zhao; Shu Chen; Jiuchun Yan (Ultrasonics Sonochemistry, 2021)
Cavitation in thin layer of liquid metal has potential applications in chemical reaction, soldering, extraction, and therapeutic equipment. In this work, the cavitation characteristics and acoustic pressure of a thin liquid Ga–In alloy were studied by high speed photography, numerical simulation, and bubble dynamics calculation. A self-made ultrasonic system with a TC4 sonotrode, was operated at a frequency of 20 kHz and a max output power of 1000 W during the cavitation recording experiment. The pressure field characteristic inside the thin liquid layer and its influence on the intensity, types, dimensions, and life cycles of cavitation bubbles and on the cavitation evolution process against experimental parameters were systematically studied. The results showed that acoustic pressure inside the thin liquid layer presented alternating positive and negative characteristics within 1 acoustic period (T). Cavitation bubbles nucleated and grew during the negative-pressure stage and shrank and collapsed during the positive-pressure stage. A high bubble growth speed of 16.8 m/s was obtained and evidenced by bubble dynamics calculation. The maximum absolute pressure was obtained at the bottom of the thin liquid layer and resulted in the strongest cavitation. Cavitation was divided into violent and weak stages. The violent cavitation stage lasted several hundreds of acoustic periods and had higher bubble intensity than the weak cavitation stage. Cavitation cloud preferentially appeared during the violent cavitation stage and had a life of several acoustic periods. Tiny cavitation bubbles with life cycles shorter than 1 T dominated the cavitation field. High cavitation intensities were observed at high ultrasonication power and when Q235B alloy was used because such conditions lead to high amplitudes on the substrate and further high acoustic pressure inside the liquid.